Intertester and intratester reliability of movement control tests on the hip for patients with hip osteoarthritis - Lenzlinger-Asprion, Rahel (BMC Musculoskelet Disord, 2017)
BACKGROUND: Hip joint complaints are a problem associated with increasing age and impair the mobility of a large section of the elderly population. Reliable and valid tests are necessary for a thorough investigation of a joint. A fundamental function of the hip joint is movement control and a test of this function forms a part of the standard examination. Until now there have been few scientific studies which specifically investigate the reliability of measurement tests of movement control of the hip joint. The aim of this study was to examine the intratester and intertester reliability of the movement control tests of the hip joint which are in use in current clinical practice. METHODS: Sixteen participants with hip joint complaints and 14 without hip joint impairment were recruited. All participants performed five active movement control tests for the hip joint and were video filmed whilst performing these tests. These films formed the basis for the evaluation and were assessed by two independent physiotherapists. For the intertester and intratester reliability calculations specially set weighted kappa values and the calculated percentages were used. RESULTS: The intertester reliability of the five examined movement control tests of the hip joint showed good to almost perfect values (weighted kappa (wk) = 0.56–0.87). The intratester reliability of the more experienced evaluator A was better in regards to the less experienced evaluator B (average wk = 0.62 vs 0.38). CONCLUSION: The visual evaluation of movement control tests of the hip joint is especially reliable when carried out by an experienced evaluator. 4 out of 5 tests also showed good results for intertester reliability and support their use in clinical practice.